You wouldn't want to be a nurse during the American Civil War! : a job that's not for the squeamish - Senior, Kathryn (You wouldn't want to--., 2010)
A study of nursing care during the Civil War, the problems with caring for the sick and the injured, and the medical advances that have been made after the war.